Hubungan Budaya Organisasi Dan Kepuasan Kerja Dengan Komitmen Organisasi Guru Honorer - Priarti Megawanti (Sosio e-Kons, 2014)
The purpose of this research are to know: (1) about correlation between culture organization and commitment organization; (2) about correlation between job satisfaction and commitment organization; (3) about correlation between culture organization and job satisfaction with commitment organization.This research had done in several state elementary schools that placed on Kramatjati, East Jakarta. The method of this research is quantitative description approach. The purpose of using this method was to analyze the correlation between two or more variable through hypothesis test and also to identificate social phenomena that happened in real situation. The result of the research answering the hypothesis which are: (1) there’s a positive correlation between culture organization and commitment organization. It has proved with the result of regression assessment ? = 43,76 + 0,408 X1 and the result of coefficient correlation assessment is 0.645; (2) there’s a positive correlation between culture organization and commitment organization. It has proved with the result of regression assessment ? = 37,61 + 0,563 X2 and the result of coefficient correlation assessment is 0,575; (3) there’s significance correlation between culture organization and job satisfaction, with the result of assessment Fcount(24,89)>Ftable(3,22). Nevertheless, if school start to improve all of them, state elementary school will have honorary teacher with high dedication.Key notes: culture organization, commitment organization, and job satisfaction